The dynamics of the entities in the judicial system – their perceived value - Martins, A.; Crespo de Carvalho, J. (EurOMA 2015 - Operations management for sustainable competitiveness, 2015)
The judicial system is bases on a network of entities. These entities influence/restrain the value provided to customers. This research aimed at identifying if customers perceive the same constraints in the judicial system as the court and to provide suggestions to increase that perceived value. Only the civil process was analysed. A focus group and a Delphi method were used. Findings show discrepancies between the internal and external perspectives of the judicial system and that the external perspective is mainly focused on issues in the judicial system outside the court. Recommendations to improve perceived value are provided.